A Person-Centered Prehabilitation Program Based on Cognitive-Behavioral Physical Therapy for Patients Scheduled for Lumbar Fusion Surgery: A Randomized Controlled Trial. Issue 8 (21st February 2019) - Lotzke, Hanna; Brisby, Helena; Gutke, Annelie; Hägg, Olle; Jakobsson, Max; Smeets, Rob; Lundberg, Mari
Abstract: Background: Prehabilitation programs have led to improved postoperative outcomes in several surgical contexts, but there are presently no guidelines for the prehabilitation phase before lumbar fusion surgery. Objective: The objective was to investigate whether a person-centered physical therapy prehabilitation program, based on a cognitive-behavioral approach, is more effective than conventional care in reducing disability and improving functioning after lumbar fusion surgery in patients with degenerative disk disease. Design: This study was a randomized controlled trial. Setting: The study took place at 2 private spine clinics and 1 university hospital. Patients: We prospectively enrolled 118 patients scheduled for lumbar fusion surgery. Intervention: The active intervention used a person-centered perspective and focused on promoting physical activity and targeting psychological risk factors before surgery. The control group received conventional preoperative care. Measurements: The primary outcome was the Oswestry Disability Index score. Secondary outcomes were back and leg pain intensity, catastrophizing, kinesiophobia, self-efficacy, anxiety, depression, health-related quality of life, and patient-specific functioning, physical activity, and physical capacity. Data were collected on 6 occasions up to 6 months postoperatively. A linear mixed model was used to analyze the change scores of each outcome. Results: No statistically significant between-group difference was found on the primary outcome (disability) over time (baseline to 6 months). Among secondary outcome measures, a statistically significant interaction effect ("Group × Time") was seen for the European Quality of Life 5 Dimensions Questionnaire. The largest between-group difference on the European Quality of Life 5 Dimensions Questionnaire index was seen 1 week prior to surgery and favored the active intervention. The largest between-group effect sizes at the 6-month follow-up favored the active intervention, and were seen for physical activity intensity, steps per day, and the One Leg Stand Test. Both groups reached the minimal important change for the primary outcome and, in several secondary outcomes (pain intensity, back and leg; pain catastrophizing; anxiety; health-related quality of life [EQ5D VAS]), already at 8-week follow-up. Limitations: The participants' preoperative level of disability was lower than normative values, which suggests selection bias. Conclusions: Both interventions led to clinically important changes, but it is not clear what kind of prehabilitation program is the most effective.